Current Applications and Future Directions of Bioengineering Approaches for Bladder Augmentation and Reconstruction - Wang, Xuesheng; Zhang, Fan; Liao, Limin (Frontiers in Surgery, 2021)
End-stage neurogenic bladder usually results in insufficiency of upper urinary tract, requiring bladder augmentation with intestinal tissue. To avoid complications of augmentation cystoplasty, tissue-engineering technique could offer a new approach of bladder reconstruction. This work reviews the current state of bioengineering progress and barriers in bladder augmentation or reconstruction, and proposes an innovative method to address the obstacles of bladder augmentation. The ideal tissue-engineered bladder has characteristics of high biocompatibility, compliance, and specialized urothelium to protect the upper urinary tract and prevent extravasation of urine. Despite that many reports have demonstrated that bioengineered bladder possessed a similar structure to native bladder, few large animal experiments and clinical applications have been performed successfully. The lack of satisfactory outcomes over the past decade may have become an important factor hindering the development in this field. More studies should be warranted to promote the popularization of tissue-engineered bladders in the clinic.